(untitled) (The South East European Journal of Economics and Business, 2020)
The central theme in this article is Consumer Social Responsibility (CnSR) in the context of sustainable water consumption at home. In this paper, a conceptual SEM model will be tested based on the Theory of Planned Behaviour. This model focuses on the role of trust mediated by CnSR attitude, in influencing water conservation behaviour. Using a sample of 493 respondents, SEM analysis results show that trust in water companies and general trust disposition have significant effect on CnSR attitude. Attitude is approached via environmental, economic and social angle, covering three (triple) mentioned domains of sustainability each with an associated minimum (bottom) required level (line) also known as the Triple Bottom Line (TBL).